Hubungan antara daya ledak otot dengan akurasi passing menggunakan kaki dalam pada siswa ekstrakurikuler futsal SMA Negeri 03 Lebong Sakti - Putra, Ari Prinando (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
This study aims to determine the correlation between muscle explosive power passing using inside foots to futsal game passing accuracy in extracurricular students of SMA NEGERI 03 LEBONG SAKTI in Academic Year of 2020/2021. The method in this research uses quantitative methods. This research is a correlation. The sample amounted of 14 students of SMA NEGERI 03 LEBONG SAKTI. Data collection used standing long jump test and passing skills tests. From the research, it was found that the value of the correlation coefficient of Muscle explosive power of the passing skills was positive, meaning that the greater the score obtained, the stronger the correlation between the two variables. The test for the significance of the correlation coefficient is carried out by means of the value r count with r table at α = 5% with N = 14, the obtained r table is 0.532 because the correlation coefficient between rx.y = 0.80> r (0.5) (14) = 0.532 means the correlation muscle explosive power with the passing accuracy skills of extracurricular students at SMA Negeri 03 Lebong Sakti is significant.